INTEGRASI TERAPI SPIRITUAL AL-QUR'AN DAN PENGOBATAN NABI DALAM PENYEMBUHAN HOLISTIK: STUDI KONSEPTUAL OLEH REHAB HATI FOUNDATION - Isdianto, Andik; Al Indunissy, Nuruddin; Fitrianti, Novariza (Wahana Islamika Jurnal Studi Keislaman, 2025)
The Qur'an is believed to have a healing dimension that is not only spiritual but also influences physical and mental health. This study examines the application of Quranic recitation-based therapy and Islamic medical practices as implemented by Rehab Hati Foundation. This research employs a qualitative method with a literature review approach to explore the concept of "7 Secrets of Quranic Healing", including the impact of sound frequencies, belief in the therapeutic process, and the application of traditional healing methods on human well-being. The analysis is conducted on various literature sources discussing the effects of spiritual-based therapy in enhancing emotional and physiological balance. The findings indicate that Quranic recitation has a positive effect in reducing anxiety, stabilizing the nervous system, and strengthening the immune system. Moreover, the integrative approach between religious therapy and conventional medical methods has the potential to become an alternative solution in preventive and rehabilitative medicine. This study concludes that this method can support a spiritual-based health system, offering benefits both psychologically and clinically.